How do individuals rate their health compared to others? findings based on a nationally representative sample in Germany - André Hajek; Hans-Helmut König (BMC Public Health, 2024)
Abstract Background The aim of this study is to explore the determinants of health comparisons (i.e., how individuals rate their health compared to other individuals in their age bracket) in the general adult population (total sample and in different age groups). Methods Data were used from the general adult population in Germany (wave 46, n = 3,876 individuals; November 2021 to January 2022), based on the GESIS panel, which is a probability-based mixed-mode panel. Health comparisons were used as outcome measure. Socioeconomic, lifestyle-related and health-related determinants were included in regression analysis. Robustness checks were conducted. Results Regressions showed that more favorable health comparisons were associated with being male (among individuals up to 39 years), higher age (among the total sample), higher education (among the total sample and individuals up to 39 years), higher income (among the total sample and individuals aged 40 to 64 years), not “being married, and living together with a spouse” (among the total sample), never eating meat (among the total sample, individuals up to 39 years and particularly individuals aged 40 to 64 years), drinking alcohol (among the total sample, individuals aged 40 to 64 years and individuals aged 65 years and over), a higher frequency of sports activities (all groups) and a higher satisfaction with health (also in all groups). Conclusion In addition to the evident link between health satisfaction and health comparisons, regression analysis revealed that certain socioeconomic factors, such as a higher income level, along with positive lifestyle-related factors - especially among middle-aged individuals - were significantly associated with more positive health comparisons. This knowledge is required in order to support individuals at risk for negative health comparisons. This is important because negative health comparisons can contribute to poor well-being and poor health outcomes.